Probing the Top Quark Flavour-Changing Neutral Current at a Future Electron-Positron Collider - Hoda Hesari; Hamzeh Khanpour; Morteza Khatiri Yanehsari; Mojtaba Mohammadi Najafabadi (Advances in High Energy Physics)
We present a study to examine the sensitivity of a future e-e+ collider to the anomalous top flavour-changing neutral current (FCNC) to the gluon. To separate signal from background a multivariate analysis is performed on top quark pair and background events, where one top quark is considered to follow the dominant standard model (SM) decay, t→Wb, and the other top decays through FCNC, t→qg, where q is a u- or a c-quark. The analysis of fully hadronic FCNC decay of the tt- pair is also presented. The 95% confidence level limits on the top quark anomalous couplings are obtained for different values of the center-of-mass energies and integrated luminosities.